Effectiveness of Normobaric Hypoxic Mask Training on VO₂ Max and Endurance Adaptations in Male Athletes Aged 20–30: An Observational Intervention Study - Giri, Harshal; Pinjara, Farukh Mohammad; Khan, Jafar; Kumar, Sunil; Katariya, Hirendra; Varade, Veenodini; Patira, Nilesh; Gupta, Sourabh; Pal, Renuka; A Choubisa, Chitrakshi (Journal of Neonatal Surgery, 2025)
This observational intervention study evaluated the physiological adaptations in 30 trained male athletes (aged 20–30 years) who completed a 12-week structured endurance training program under normobaric hypoxic conditions using high-altitude simulation masks. The training program consisted of 5 weekly sessions combining moderate-intensity continuous runs, high-intensity intervals, tempo runs, and aerobic conditioning on treadmills, air rowers, and tracks—while wearing hypoxic masks (FiO₂ ~15%, simulating ~2500 m altitude). Key outcome measures included VO₂ max, lactate threshold, hemoglobin concentration, and resting heart rate. After 12 weeks, athletes exhibited a statistically significant improvement in VO₂ max (mean increase of 5.2 ± 1.4 mL·kg⁻¹·min⁻¹, p < 0.001), enhanced lactate threshold (average increase of 6.8%), and elevated hemoglobin levels (+0.9 g/dL). Resting heart rate showed a significant decline (−5.4 bpm). Subjective feedback indicated greater exertion during initial sessions but reported improved recovery and performance perception over time. These results support the use of normobaric hypoxic training for endurance performance enhancement in already-trained athletes.